Non-Destructive Evaluation of Oil and Free Fatty Acid Content of Oil Palm Fresh Fruit Bunch Based on Thermal Properties Using Partial Least Square (PLS) - Guspa, Monica; Makky, Muhammad; Santosa, Santosa; Cherie, Dinah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Indonesia is the largest producer of palm oil in the world, contributing 59 % of global production in 2022. The palm oil industry is a pillar of the economy and a source of foreign exchange through agricultural exports. To increase productivity and global competitiveness, strategies are needed, including improving cultivation technology and determining optimum harvest times through the application of appropriate cultivation technology. This research aims to increase oil palm productivity by focusing on the harvest time of Fresh Fruit Bunches (FFB). The sample used was Tenera variety palm FFB with two levels of ripeness, namely 140-160 DAP and 200-220 HSP. Non-destructive technology can accurately measure the optimum ripeness level of FFB. This approach uses thermal camera technology for nondestructive evaluation, recording the intensity of infrared radiation from TBS. All measurement parameters resulting from thermal image processing (RGB, L*a*b and temperature) will be used as input variable data to be modeled with oil content free fatty acid data in the laboratory. The model design will be built using the Principal Component Analysis (PCA) and Partial Least Square (PLS) methods. The results showed that the coefficient of determination (R2) for oil content was 0.8681 and free fatty acid content was 0.786. Keywords: FFB, Nondestructive, Oil content, PLS, Thermal properties